Domain and Language Choice by Three Generation of Sama Bajau Ethnic (International Online Journal of Language, Communication, and Humanities (INSANIAH), 2020)
The Bajau Sama is the second largest ethnic group in Sabah. The main ethnic settlement of Bajau Sama in Sabah is located at Kota Belud on the West Coast. As a bilingual community, the choice of language by this Muslim community varies according to generations and domains which may not favor the native language. The Domain Analysis Theory (Fishman) is applied to study the choice of language in a specific domain by participants from Kampung Taun Gusi, Kota Belud, Sabah. Survey methods with questionnaires were used to obtain information from the first (GI), second (GII) and third (GIII) generations. The mean value for each group in the family domain indicated that the GI and GII used more language Bajau Sama while the GIII tendency was towards Malay. In the neighborhood domain, GI has chosen Bajau Sama language but GII and GIII preferred BM. However, in education, religious services, and purchasing domains, all generations preferred Malay. The most important finding was the younger generation (GIII) has shifted to Malay in the family domain and in all public domains. This generation acted as a catalyst for language shift which posed a threat to the Bajau Sama language vitality even in informal domains such as family and neighborhood. This finding shows there is a decline in the intergenerational language transmission of the mother tongue among the Bajau Ethnic communities.
Keywords: Bajau Sama; domain analysis; generation of speakers; Malay; language shift